Pelatihan Alat Musik Hadrah Dalam Membentuk Karakter Anak - Meryna Putri Utami; Sriyanti; Ahmad Saputra (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2023)
Music is related to intelligence. Listening to music or learning music can develop speech, hearing, self-confidence, and can optimize children's intelligence. This research was conducted in Aman Jaya Village, Kec. North Sungkai Kab. North Lampung. This research aims to foster attitudes or character education in children through hadrah musical instrument training because it can preserve a culture that has begun to disappear. The subjects of this study were children living in Aman Jaya Village, specifically Rt 003 with a total of 22 children consisting of 11 male students and 11 female students. From the hadrah activities there were also many things that were learned from vocal exercises, practicing hadrah own musical instruments and singing Islamic songs. Based on the research data that has been collected, it is possible to cultivate a child's character attitude by carrying out Islamic activities, for example learning the hadrah musical instrument by listening to religious poetry.